A novel cleaner for colloidal silica abrasive removal in post-Cu CMP cleaning*Project supported by the Specific Project Items No. 2 in National Long-Term Technology Development Plan (No. 2009zx02308-003) and the Hebei Province Department of Education Fund (No. QN2014208). (October 2015) - Deng 邓, Haiwen 海文; Tan 檀, Baimei 柏梅; Gao 高, Baohong 宝红; Wang 王, Chenwei 辰伟; Gu 顾, Zhangbing 张冰; Zhang 张, Yan 燕
Abstract: A novel cleaning solution, named FA/O alkaline cleaner, was proposed and demonstrated in the removal of colloidal silica abrasives. In order to remove both the chemical and physical absorbed colloidal silica abrasives, an FA/OII chelating agent and non-ionic surfactant were added into the cleaner. By varying the concentration of chelating agent and non-ionic surfactant, a series of experiments were performed to determine the best cleaning results. This paper discusses the mechanism of the removal of colloidal silica abrasives with a FA/O alkaline cleaner. Based on the experiment results, it is concluded that both the FA/OII chelating and non-ionic surfactant could benefit the removal of colloidal silica abrasives. When the concentration of FA/OII chelating agent and FA/O non-ionic surfactant reached the optima value, it was demonstrated that silica abrasives could be removed efficiently by this novel cleaning solution.